Peran Ayah dalam Pendidikan Islam Anak Perempuan - Dian Febrianingsih; Putri Nur Indah Sari (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Abstract: This study aims to describe and analyze the role of fathers in family Islamic education. The purpose of the research is to increase the treasury of knowledge for educational researchers, especially the education of girls in the family. The research used is qualitative research with case studies aimed at obtaining a complete and in-depth description. Data collection is done by observation, interviews and documentation. Data analysis was performed with the concept of data triangulation. Qualitative research data analysis techniques through data triangulation are analyzing the results of interviews by checking the validity of the data which includes sources, methods, investigators, and theories. Data analysis shows that fathers as research subjects are willing to be directly involved in education and childcare. The willingness of subjects to provide Islamic education to their daughters is motivated by factors of psychological well-being, personality, attitudes and diversity (religiosity). Planting the faith, sharia and morals of fathers in daughters since their daughters are small. Even since the child is still in the womb of his wife. They use educational methods such as educating by example, habits, advice, attention, and punishment. Certainly the father established good cooperation with his wife in providing Islamic education to his daughter. So that girls will form Islamic individuals and are accustomed to carrying out daily activities according to Islamic teachings.